Development of BIM Roles in Infrastructure Projects - SULEYMANSHAR, ÎVAN; Saleh, Shairdel (My University, 2018)
This study focuses on the current BIM roles and their development within a small infrastructure consultant company referred to as OfficeBIM in the study. It is conducted with the help of a questionnaire, complementary interviews and personal observations at the company office in Gothenburg, Sweden. The study demonstrates that there are problems with definitions of the existing BIM roles and their responsibilities. Even so, new BIM roles are emerging as well. One of these new roles under construction at OfficeBIM is a “BIM supervisor”. In addition, the BIM role titles can differ among companies and countries. In this study, the role of a BIM manager is regarded as “Business Area Responsible in 3D/BIM” or the role of a BIM modeler is referred to as “3D/BIM Designer” at the company examined. Whereas, in other cases the role titles can be the same between companies and the literature, such as the role title of BIM coordinator at OfficeBIM which was consistent with the literature. The company has also recently managed to create a manual, in which all BIM roles’ responsibilities have been defined respectively. However, many of the BIM actors have the belief that the manual is mainly for guidance for newly recruited employees to know what is expected from them to deliver. In contrast, they believe a BIM actor shall know as much knowledge as possible, as BIM itself is rather broad. Thus, the BIM actors depend on each other’s skills and constantly work as a chain in BIM projects where everyone in reality knows a bit of everything. When it comes to BIM assistance in infrastructure projects, BIM actors of this study believe that time and cost saving along with useful information, competitive advantages and effective work processes are among the most beneficial factors of BIM utilized for infrastructure.
Keywords: Samhällsbyggnadsteknik; Civil Engineering